Pengaruh Pengetahuan Produk, Media Promosi Dan Word Of Mouth Terhadap Pemahaman Masyarakat Memilih Bank Syariah - Riki Pransiska; Ambok Pangiuk; Ahsan Putra Hafiz (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Bank financial institutions in Indonesia can generally be divided into Islamic banks and conventional banks. Basically, both Islamic banks and conventional banks carry out activities to collect and distribute funds to the public, but all forms of activities carried out by Islamic banks must be in accordance with sharia principles. Competition between Conventional Banks and Islamic Banks in Indonesia is one of the things that has become the focus of attention of banking managers, especially with regard to customers, moreover, Indonesian Islamic Banks are still relatively new as a result of the unification of several Islamic Banks. This study aims to see how much influence product knowledge, promotions and word of mouth have on people's understanding of choosing Islamic banks. This research is a research with a quantitative approach and uses primary data. The population in this study is the people of Jambi City, especially those who adhere to Islam. The population in this study is the people who adhere to Islam in the city of Jambi, which is 612,162 people. The sampling technique used is probability sampling so that the number of samples used is 100 respondents. The results of the study show that together the variables of product knowledge, promotion and word of mouth influence people's understanding of choosing Islamic banks. Likewise with the individual, the results of the study show that the variables of product knowledge, promotion and word of mouth have an effect on people's understanding of choosing an Islamic bank with the significance level of each variable being the same, namely equal to 0.000 and the tcount value of each variable is 3.809 for X1, 3,617 for X2 and 5,823 for X3.